Blockchain Technology in Human Resource Management: Role in the World of Work - Imas komariyah (Jurnal Info Sains : Informatika dan Sains, 2023)
This research aims to investigate the role of blockchain technology in human resource management, especially in the world of work. Blockchain technology, which has become known for its security, transparency, and ability to manage data efficiently, has the potential to change the human resource management landscape. A qualitative research approach was used to analyze how blockchain technology can be integrated in the employee selection and recruitment process. Through a comprehensive literature review, we discuss the basic concepts of blockchain technology, security principles, and applications of blockchain in various industries. Apart from that, we also explore the basic concepts of human resource management, focusing on employee selection and recruitment. If we consider the industries and sectors that can benefit most from blockchain technology, it cannot be denied that the Human Resources (HR) department is one of the most prominent. Blockchain's key advantages in data management, combined with its ability to operate globally, make it a very suitable solution for the HR field. This technology enables HR to manage sensitive information with a high level of security and transparency, and facilitates processes such as payroll, recruitment, and performance management with unmatched efficiency and accuracy. Thus, blockchain brings positive changes in the way HR manages data and optimizes their operations in an increasingly complex and globally connected work environment.